Synthetic Microfiber and Microbead Exposure and Retention Time in Model Aquatic Species Under Different Exposure Scenarios - Bour, Agathe; Hossain, Shahadat; Taylor, Mark; Sumner, Mark; Carney Almroth, Bethanie (Frontiers in Environmental Science, 2020)
Synthetic microfibers have been reported in most aquatic environments and represent a large proportion of environmental microplastics. However, they remain largely under-represented in microplastic ecotoxicity studies. The present study aims to investigate particle interaction with, and retention time in, aquatic organisms comparing microfibers and microbeads. We used brine shrimp (Artemia sp.) and fish (Gasterosteus aculeatus) as invertebrate and vertebrate models, respectively. Organisms were exposed to a mixture of microbeads (polyethylene, 27 – 32 µm) and microfibers (dope dyed polyester; 500 µm-long) for 2h, at high concentrations (100 000 part./L) in order to maximize organism-particles interaction. Artemia were exposed in presence or absence of food. Fish were exposed either via the trophic route or directly via water, and water exposures were performed either in freshwater or seawater. In absence of food, Artemia ingested high numbers of microbeads, retained in their digestive tract for up to 96h. Microfiber ingestion was very limited and their egestion fast. In presence of food, no microfiber was ingested, microbead ingestion was limited and egestion was fast (48h). Limited particle ingestion was observed in fish exposed via water, and particle retention time in gut did not exceed 48h, both for direct and trophic exposure. However, water exposures resulted in higher number of particles present in gills, and average retention time was higher in gills, compared to gut. This suggests that gills are organs susceptible to microplastic exposure, and should be taken into account in fish exposure and effect studies. Our results show that particle ingestion and retention by organisms differ between microbeads and microfibers, suggesting particle selection based on size, shape and/or color, and species-specific selective feeding. We also showed that the presence of food results in limited particle ingestion and retention in Artemia, and that microbeads are more likely to be transferred to organisms from upper trophic levels than microfibers. Finally, fish exposure to particles was not significantly different between freshwater and seawater conditions.